Profilaktyka, diagnoza, terapia – podstawą prawidłowej pracy pedagoga - Szczepańska, Magdalena (Wydawnictwo Naukowe, 2010)
Materiał zebrany przez H. Krauze-Sikorską i K. Kuszak przesycony jest dużą ilością ważnych zagadnień i stanowi doskonały zarys wiedzy na temat postępowania pedagogicznego wobec dziecka z trudnościami. Skierowany jest zarówno do pedagogów, nauczycieli, wychowawców, terapeutów, psychologów, studentów pedagogiki. Kompetencje z zakresu profilaktyki, diagnozy i terapii pedagogicznej są niezbędne, by stworzyć właściwy system pomocy dziecku.

The material assembled by H. Krauze-Sikorska and K. Kuszak is satiated with a large amount of important questions and is a perfect outline of knowledge about pedagogical procedure in accordance with developmental difficulties. The material is directed towards pedagogues, teachers, tutors, therapists, psychologists and the students of pedagogics. The competences in prophylactics, diagnosis and pedagogical therapy are imperative towards the construction of a proper system of pedagogical and psychological help.
Prophylactics, diagnosis, therapy – the correct basis of the pedagogues work
Keywords: diagnoza; diagnosis; terapia; therapy; profilaktyka; prophylactics; zaburzenia; disorders